Sinensetin: An Insight on Its Pharmacological Activities, Mechanisms of Action and Toxicity - Han Jie, Lee; Jantan, Ibrahim; Yusoff, Syaratul Dalina; Jalil, Juriyati; Husain, Khairana (Frontiers in Pharmacology, 2021)
Sinensetin, a plant-derived polymethoxylated flavonoid found in Orthosiphon stamineus Benth. and several citrus fruits, has been found to possess strong anticancer activities and a variety of other pharmacological benefits and promising potency in intended activities with minimal toxicity. This review aims to compile an up-to-date reports of published scientific information on sinensetin pharmacological activities, mechanisms of action and toxicity. The present findings about the compound are critically analyzed and its prospect as a lead molecule for drug discovery is highlighted. The databases employed for data collection are mainly through Google Scholar, PubMed, Scopus and Science Direct. In-vitro and in-vivo studies showed that sinensetin possessed strong anticancer activities and a wide range of pharmacological activities such as anti-inflammatory, antioxidant, antimicrobial, anti-obesity, anti-dementia and vasorelaxant activities. The studies provided some insights on its several mechanisms of action in cancer and other disease states. However, more detail mechanistic studies are needed to understand its pharmacological effects. More in vivo studies in various animal models including toxicity, pharmacokinetic, pharmacodynamic and bioavailability studies are required to assess its efficacy and safety before submission to clinical studies. In this review, an insight on sinensetin pharmacological activities and mechanisms of action serves as a useful resource for a more thorough and comprehensive understanding of sinensetin as a potential lead candidate for drug discovery.